Using genomics to combat infectious diseases on a global scale. Issue 1 (December 2015) - Cain, Amy; Lees, John
Abstract A report on the seventh annual Infectious Disease Genomics Conference, held in Hinxton, Cambridge, UK, 14–16 October 2015.